A new genus and species of Tarsonemidae (Acari: Heterostigmata) from the Atlantic Forest, Brazil - Lofego, Antonio C.; Demite, Peterson R.; Moraes, Gilberto J. De (Zootaxa, 2015)
Kaliszewskia ochoai gen. nov., sp. nov. (Tarsonemidae: Tarsoneminae: Tarsonemini) is described from adult females, collected on Blepharocalix salicifolius (Kunth) O.Berg and Plinia sp. (Myrtaceae), from the Atlantic Forest in Brazil.